The centrality of the machine in the thought of Jacques Lafitte - Sandrone, Darío Rubén (2022)
Jacques Lafitte occupies an odd place in the philosophy of technology. He was a French engineer who made a significant and conceptually innovative contribution to this field, yet his influence has been elusive and largely ignored until relatively recently. Many of Lafitte’s ideas find echoes in the work of later philosophers (particularly Gilbert Simondon), yet, notably in the case of Simondon, apparently without any direct line of influence. Lafitte placed the machine at the centre of his thinking about technology and articulated various layers of analysis around it; for example, he considered machines in the broader context of an artificial world or “mechanosphere”, which encompassed certain aspects of philosophical anthropology (namely, how to think the human in the context of human–machine relations, in the context of socio-political organizations). In this work we seek to reconstruct Lafitte’s ideas and briefly trace some of their later impact. We identify three dimensions (or theses) in Lafitte’s analysis: epistemological, ontological and anthropological. We argue that the most remarkable fact about Lafitte’s thought is the way it inaugurates, and anticipates, the approach of later currents, not just in the “French tradition”, who also made an effort to integrate machine theory into broader philosophical, anthropological and political aspects, in terms that echo Lafitte’s. In particular, we will focus on Gilbert Simondon and cybernetics.